Higher Education and Web 2.0: Theory and Practice - Isaias, Pedro; Pifano, S.; Miranda, P. (IGI Global, 2013)
The inclusion of Web 2.0 in education has been a polemic process comprised both with enthusiasm and scepticism. There is empirical evidence of Web 2.0's effective employment in educational contexts and it seems that the background of hesitation that has always accompanied Web 2.0's didactic progress is now more concentrated on questioning how to use it rather than whether or not it should be used. In light of this predicament, this chapter aims to analyse how some Web 2.0 tools are being used in higher education as well as to uncover what best practices should guide their successful deployment. This chapter begins by providing an overview of the advantages and disadvantages of using Web 2.0 pedagogically, and it then focuses on particular cases where educators have experimented with YouTube, wiki technology, and Twitter in their teaching settings. The lessons learned and the outcomes of their experiences are combined with current theory on Web 2.0 in education to serve as guidelines.